Waste cooking oils as processing aids for eco-sustainable elastomeric compounding. Issue 1 (February 2022) - Cherubini, Valeria; Lamastra, Francesca Romana; Bragaglia, Mario; Nanni, Francesca
This work focuses on the replacement of mineral oils with bio-based waste cooking oils in rubber compounding. Two different waste cooking oils from potatoes and chicken frying process were analyzed by means of chemical and rheological tests to evaluate the chemical composition, the oxidative stability and the viscosity. Waste oils have been introduced in elastomeric compounds as substitute for typical processing aids (i.e. lubricants). Cure kinetics of rubber compounds was studied by rheological characterization. Mechanical properties of vulcanized samples were determined by means of tensile tests, hardness tests and dynamic mechanical analysis. The waste oils showed a rheological behavior very similar to the mineral oils conventionally employed in rubber manufacturing leading to almost the same processability of the resulting compound. The waste oils did not significantly affect the vulcanization kinetics of the rubber compound, as expected for conventional lubricants. Waste cooking oils and mineral oil show analogous influence on mechanical properties of cured compounds. At increasing oil content, the elongation at break and the tensile strength increased whereas the values of Elastic Modulus at 100% strain, the Storage Modulus and Shore A Hardness decreased with respect to the oil-free sample. These results are very promising, confirming the possibility to replace the mineral oils, in a good practice of circular economy.